If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -5 = 3x + 2whatisx Reorder the terms: -5 + x = 3x + 2whatisx Reorder the terms: -5 + x = 2ahistwx + 3x Solving -5 + x = 2ahistwx + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2ahistwx' to each side of the equation. -5 + -2ahistwx + x = 2ahistwx + -2ahistwx + 3x Combine like terms: 2ahistwx + -2ahistwx = 0 -5 + -2ahistwx + x = 0 + 3x -5 + -2ahistwx + x = 3x Add '-3x' to each side of the equation. -5 + -2ahistwx + x + -3x = 3x + -3x Combine like terms: x + -3x = -2x -5 + -2ahistwx + -2x = 3x + -3x Combine like terms: 3x + -3x = 0 -5 + -2ahistwx + -2x = 0 Add '5' to each side of the equation. -5 + -2ahistwx + 5 + -2x = 0 + 5 Reorder the terms: -5 + 5 + -2ahistwx + -2x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -2ahistwx + -2x = 0 + 5 -2ahistwx + -2x = 0 + 5 Combine like terms: 0 + 5 = 5 -2ahistwx + -2x = 5 Reorder the terms: -5 + -2ahistwx + -2x = 5 + -5 Combine like terms: 5 + -5 = 0 -5 + -2ahistwx + -2x = 0 Factor out the Greatest Common Factor (GCF), '-1'. -1(5 + 2ahistwx + 2x) = 0 Ignore the factor -1.Subproblem 1
Set the factor '(5 + 2ahistwx + 2x)' equal to zero and attempt to solve: Simplifying 5 + 2ahistwx + 2x = 0 Solving 5 + 2ahistwx + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + 2ahistwx + -5 + 2x = 0 + -5 Reorder the terms: 5 + -5 + 2ahistwx + 2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2ahistwx + 2x = 0 + -5 2ahistwx + 2x = 0 + -5 Combine like terms: 0 + -5 = -5 2ahistwx + 2x = -5 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 1=21 | | y=-6(4)+24 | | -15c/-4 | | 3(-6x+24)-x+4=0 | | -0.5(5x-2)=-3(0.5x-2)-1 | | 453.6672=(3.14*r^2)+(3.14*r^2)+(13*r*6.28) | | 5.7x-5=3(x-0.7)-11 | | 0.3(0.1-0.5)=1.2 | | y/3-7=-5 | | 0.6(2x-1)=0.4x-1.4 | | 25.748=(3.14*r^2)+(3.14*r^2)+(3.1*r*6.28) | | 2x^2-12+8=0 | | 0.2(x+1)=1.8 | | 0.3x+1.4=0.6x-1 | | 3x^3*4= | | 0.2x+1.9=-x+4.3 | | 0.72x+0.21=0.64x-0.27 | | 0.03x-0.12=0.01x+0.02 | | 3x^3(1x+4)= | | x^2+xm-1=0 | | 21x-30=10+21 | | 11x-x^2-28=0 | | 0=x^2-11x+22 | | y+11x=36 | | 8x+7y=2x+y | | 3x*1x= | | 5651.8116=(3.14*r^2)+(3.14*r^2)+(55.6*r*6.28) | | 30=-5/9w | | 16b=-496 | | F(x)=40-2(12) | | 40+30p=190 | | 21x+8=6 |